Perinatal free carnitine and short chain acylcarnitine blood concentrations in 12,000 full-term breastfed newborns in relation to their birth weight - Penelope D. Manta-Vogli; Kleopatra H. Schulpis; Yannis L. Loukas; Yannis Dotsikas (Elsevier, 2020)
Background: Free carnitine (C0) and short chain acylcarnitine (SCA) blood concentrations play a significant role in fatty acid oxidation process during the first days of life. The aim of this study was to demonstrate C0 and SCA concentrations in Dried Blood Spots (DBS) of full term breastfed infants in relation to their birth weight (BW) perinatally. Methods: Breastfed full term infants (n = 12,000, 6000 males, 6000 females) with BW 2000-4000 g were divided into 4 equal groups: Group A, 2000-2500 g, B 2500-3000 g, C 3000-3500 g and D 3500-4000 g. Blood samples in the form of DBS were collected on the 3rd day of life and analyzed via a liquid chromatography tandem mass spectrometry (LC-MS/MS) protocol. Results: BW-related C0 and SCAs were found as follows: C0 was determined to be statistically significantly higher in group A (BW 2000-2500 g) in both males and females. Lower acetylcarnitine (C2) and hydroxybutyrylcarnitine (C4OH) blood concentrations were detected in group A of both sexes, whereas butyrylcarnitine (C4) concentrations were found to be lower in the same group of males only. Furthermore, high concentrations of C2 and C4OH were shown in group D (BW 3500-4000 g) in both sexes. SCA sum of means ± SD values in males and females of group A were statistically significantly lower as compared to other study groups. Conclusion: Due to the number of the samples, data from this study could be applied as neonatal screening reference values for full term breastfed newborns in relation to their birth weight.